PERBANDINGAN DAYA HAMBAT DARI EKSTRAK DAN HASIL FERMENTASI BAWANG PUTIH (Allium sativum) TERHADAP BAKTERI Escherichia coli - Oom Komala; Putri Dwi Antini; Novi Fajar Utami (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2022)
Allium sativum is a plant that generally grows in the highlands and is used to treat digestion, anti-inflammatory, hypertension. Meanwhile, fermented onions are fermented garlic for 40 days and are used as medicine for diabetes, hypertension, hypercholesterolemia. These fermented garlic and fresh garlic contain alkaloids, flavonoids, saponins, and tannins. The purpose of this study was to compare the antibacterial activity of fermented garlic and garlic by determining the minimum inhibitory concentration (MIC) and Inhibitory Width (LDH) against E. coli bacteria. Method: Garlic fermentation is done by wrapping fresh garlic in aluminum foil and putting it in a rice cooker for 40 days. MIC test at concentrations of 20%, 25%, 50% and 75% with agar dilution method and LDH test with disc diffusion method at concentrations of 25%, 50% and 75%. The results showed that fermented garlic and garlic extracts were able to inhibit E. coli bacteria with the Minimum Inhibitory Concentration (MIC) at a concentration of 25%. Garlic extract is the most optimal extract at a concentration of 75% having antibacterial activity compared to fermented onion extract with an average Inhibitory Width (LDH) of 7.43 mm in the medium category. Conclusion: fresh garlic extract had better antibacterial activity than fermented garlic extract against E. coli.